2022
DOI: 10.1101/2022.06.04.494803
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Host preference and survivorship ofEuschistus heros(Hemiptera: Pentatomidae) strains on cotton and soybean

Abstract: The Neotropical brown stink bug Euschistus heros (Fabricius) (Hemiptera: Pentatomidae) is a key pest of soybeans, Glycine max, and recently became an economically important pest of cotton, Gossypium hirsutum. This stink bug has two allopatric strains, one prevalent in southern Brazil (SS), and another in the north (NS). The two strains hybridize in central Brazil. Knowledge of host preferences and host suitability of these strains can clarify the contribution of the different gene pools to contemporary adaptiv… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 49 publications
(57 reference statements)
3
1
0
Order By: Relevance
“…A similar trend was found in a recent survey carried out in the central and southern regions of Brazil 37 . Factors that could explain these results include the superior capability of Euschistus heros among native species to survive in agroecosystems and the efficient use of soybean plants (an exotic host) as a food resource 20,40,41 …”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…A similar trend was found in a recent survey carried out in the central and southern regions of Brazil 37 . Factors that could explain these results include the superior capability of Euschistus heros among native species to survive in agroecosystems and the efficient use of soybean plants (an exotic host) as a food resource 20,40,41 …”
Section: Discussionsupporting
confidence: 79%
“…The stink bug must undergo a complex adaptation process, including the recognition of soybean as a host and dealing with morphological and chemical soybean defenses against herbivory. 40,41 We confirmed that Euschistus heros is the main soybean pest in Brazil, with minor alterations in seasonal dynamics among soybean macroregions. The high prevalence of adults over nymphs during the R1 and R2 stages is possibly related to adults moving continuously to soybean fields in search for food resources.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations